PENGELOLAAN LIMBAH PERTANIAN TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN BAWANG MERAH (Allium ascalonicum L.) - Hakim, Tharmizi; Budianto, Rhiki (Universitas Pembangunan Panca Budi, 2021)
Shallots (Allium ascalonicum. L) have long been cultivated by farmers in Indonesia as commercial farming. In increasing the production of shallots, maximum nutrients are needed, with the use of mixed compost and mixed POC root nodules. This research method used a factorial Randomized Block Design (RAK) consisting of 2 factors with 16 treatment combinations and 2 replications. The factors that must be studied are the main factors in the treatment of mixed compost (JC) consisting of 4 levels, JC0 = Control, JC1 = 1 Kg/plot, JC2 = 2 Kg/plot, and J3 = 3 Kg/plot. The second factor was mixed root nodule POC (BA) consisting of 4 levels, namely BA0 = Control, BA1 = 100 ml/liter water/plot, BA2 = 200 ml/liter water/plot, BA3 = 300 ml/liter water/plot. The parameters of this study were the number of leaves per sample aged 2,3,4 and 5 WAP (strands), wet tubers per sample (g), dry tubers per plot (g), production conversion per Ha (kg). The results showed that the mixed mixture treatment had a very significant effect on the parameters of the number of leaves per sample (strands), dry tubers per plot (g), and production conversion per hectare (kg), but had a significant effect on the parameters of wet tubers per hectare (g). The use of mixed root nodule POC had a very significant effect on the number of leaves per sample (strands), dry tubers per plot (g), and production conversion per Ha (kg), but had a significant effect on wet tuber parameters per sample (g). The interaction of mixed utilization and POC of mixed root nodules did not have a significant effect on all parameters.